Antjie Krog, self and society: the making and mediation of a public intellectual in South Africa - Garman, Anthea (My University, 2010)
Abstract In post-colonial, post-apartheid South Africa, the avowedly Africanist, nationalist government has taken seriously that as part of the functioning of democracy, this new nation needs a vibrant public space for the airing of ideas and the formation of public opinion. Thus, a crucial priority for the functioning of the public sphere is the widening of the public domain, beyond the participation of the bourgeoisie, to facilitate the inclusion of the voices of the black majority. But, an interesting – and volatile – dimension of the South African public sphere is the rhetoric about its parlous state, and a strong concern with who populates this public sphere and what ideas they put into public. A great many “calls” have been made for various types of intellectuals to take up public positions and contribute to the healthiness of public life. Coupled with these calls are statements invoking Edward Said’s style and ideas about public intellectual representation, and the phrase “speaking truth to power” (with a multiple interpretations) has become a familiar one in these debates in South Africa. There are furious discussions about styles of engagement, suitable subject matter, sources of authority, vested interests and arguments about degrees of independence. A notable feature of these debates is that they are often couched in the language of “crisis” which, I argue, points not to the overt dangers being espoused, but another one entirely – a crisis about what constitutes authority to speak in public and to be a proxy for those who cannot or do not speak. This sense of “crisis” in the South African public sphere has echoes all over the world where similar debates about the public domain and public intellectuals are also taking place. Asserting that these debates are evidence of a deep anxiety about authority and legitimacy, I have chosen to focus on one particular public figure in South Africa, Antjie Krog, the poet, journalist and book author, who for four decades has found a public and a hearing for her ideas. In a time when white Afrikaners have been dispossessed of social and political power, it is remarkable that Krog has both platform and voice, when who speaks for whom and on what issues in the South African public space is so fraught. I argue that the study of Krog shows that the ability to speak in public is more than simply a matter of agency and the acquisition of skilled speech and the facility of representation (as in Said’s formulation of what makes a public intellectual). This thesis asserts that the agency to speak is powerfully connected to accumulated authority and that an investigation of the makers and markers of authority enables an understanding of how a particular person comes to have a platform in public, despite dramatically shifting social and political circumstances. The case study of Krog shows that the literary aesthetic, and an adaptive subjectivity responsive to the ethical, combined with accumulated authority acquired across fields and married to the power of media attention, is what gives this white, Afrikaans-speaking woman poet her voice and hearing in South Africa today.